(untitled) (Mustansiria Dental Journal, 2018)
The ProTaper rotary retreatment files is one of the new files especially designed for retreatment. The aim of this study is to test if root canals filled with Resilon points and RealSeal sealer (SybronEndo, USA) can be retreated using ProTaper rotary retreatment files in the same manner as canals filled with gutta-percha and zinc oxide eugenol based sealer. Twenty extracted maxillary first molars with palatal roots having single straight canal and fully formed apex were instrumented and randomly divided into two groups of ten roots each according to the root filling material used (gutta-percha and zinc oxide eugenol based sealer for group A and Resilon points and RealSeal sealer for group B). For all roots, removal of root filling material was done by using ProTaper rotary retreatment files (Dentsply-Maillefer, Ballaigues, Switzerland). The amount of root filling material remained and the time required for the removal process for all roots were recorded and statistically analyzed using SPSS version 15. The results showed that during retreatment procedures; removal of Resilon with RealSeal sealer from root canals can be achieved with ProTaper rotary retreatment files but the amount of Resilon root filling material remained was more than GP and showed a highly significant difference, it was also obvious that removal of Resilon root filling material from root canals requires more time than roots filled with guttapercha. In conclusion, removal of resin based root filling material can be achieved with ProTaper rotary retreatment files but it leaves more filling remnants and takes more time than canals filled with gutta-percha.